CAREER OPTIONS IN SECURITIES MARKETS - Dr. Ramesha V; Sumathi S; Kalaivani K; Lakshmi V (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The research article focus on three things such as Career, Options and Securities Markets. So, the student in the school days itself should have career planning for a better career development in the future long run. The study is based on secondary data. So, the data has been taken from various secondary sources like, Google, Youtube videos, Facebook, daily newspapers etc. Career refers to an occupation or profession planned by an individual. It is a long term plan must be done by himself for better success in his life. It is observed that career planning helps for career development. So, students and employees must have passion of learning either online or offline programs. NISM has around thirty three certification activities for capacity building among Indian passionate graduates. Both online and offline free classes are done to make use of certificate programs. 250 plus exam centers are available across India to give exams to validate certificate courses. There is a concept of ATM (Alternative Time Management) which says that students must shift their valuable time from wasting activities (Social Media) to productive activities. This increase the productivity of candidates in their career development. ASK model can be applied in this regard.